Trumpet omnibook for B♭ instruments : transcribed exactly from artist recorded solos - Adderley, Nat 1931-2000; Armstrong, Louis 1901-1971; Beiderbecke, Bix 1903-1931; Eldridge, Roy 1911-1989; Gillespie, Dizzy 1917-1993; Hirt, Al 1922-1999; James, Harry 1916-1983; Dankworth, E. 1961-; Morgan, Lee 1938-1972; Navarro, Fats 1923-1950 (Hal Leonard, 2018)
47 transcriptions of songs played by Nat Adderley, Herb Alpert, Louis Armstrong, Chet Baker, Bix Beiderbecke, Randy Brecker, Clifford Brown, Miles Davis, Roy Eldridge, Art Farmer, Maynard Ferguson, Dizzy Gillespie, Bobby Hackett, Roy Hargrove, Tom Harrell, Al Hirt, Freddie Hubbard, Harry James, Ryan Kisor, Chuck Mangione, Wynton Marsalis, Lee Morgan, Fats Navarro, Nicholas Payton, Arturo Sandoval, Jack Sheldon, Rex Stewart, and Clark Terry